2011
DOI: 10.1093/aob/mcr192
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-five years of progress in understanding pollination mechanisms in palms (Arecaceae)

Abstract: Visitors to palm inflorescences are attracted by rewards such as food, shelter and oviposition sites. The interaction between the palm and its visiting fauna represents a trade-off between the services provided by the potential pollinators and the antagonistic activities of other insect visitors. Evidence suggests that beetles constitute the most important group of pollinators in palms, followed by bees and flies. Occasional pollinators include mammals (e.g. bats and marsupials) and even crabs. Comparative stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
97
2
6

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(112 citation statements)
references
References 77 publications
7
97
2
6
Order By: Relevance
“…The pollination of the species is still under discussion. Indeed, despite former proposals of several insects -notably beetles-as pollinators (Barfod et al, 2011), it has been suggested recently that M. flexuosa is a wind-pollinated species (Korshand Rosa & Koptur, 2013). This palm is widely distributed across tropical South America at both sides of the Equator, between approximately 12º N and 20º S, but it is restricted to the Orinoco and the Amazon lowlands being absent from the Andes, the Pacific coasts and most of the Brazilian Atlantic coasts (Fig.…”
Section: Biogeographical and Ecological Overviewmentioning
confidence: 99%
“…The pollination of the species is still under discussion. Indeed, despite former proposals of several insects -notably beetles-as pollinators (Barfod et al, 2011), it has been suggested recently that M. flexuosa is a wind-pollinated species (Korshand Rosa & Koptur, 2013). This palm is widely distributed across tropical South America at both sides of the Equator, between approximately 12º N and 20º S, but it is restricted to the Orinoco and the Amazon lowlands being absent from the Andes, the Pacific coasts and most of the Brazilian Atlantic coasts (Fig.…”
Section: Biogeographical and Ecological Overviewmentioning
confidence: 99%
“…In the tropics, the most representative genera are Apis and Trigona. These genera are considered generalist pollen and nectar feeders that are attracted to flowers by color cues (Baford et al 2011). They make their nest in the proximity of palms and transport pollen grains as a food source (Henderson et al 2000, Sakai 2002.…”
Section: Pollinator Diversity In Elaeis Palmsmentioning
confidence: 99%
“…However, they are always found in small numbers (Baford et al 2011). Thus, there is still much research to be done to reveal the precise role of this group of insects as efficient pollinators.…”
Section: Pollinator Diversity In Elaeis Palmsmentioning
confidence: 99%
See 1 more Smart Citation
“…A família Arecaceae possui representantes por toda a região tropical e subtropical do globo, sendo considerada uma importante fonte de recursos para a sobrevivência de diferentes comunidades (ZAMBRANA et al, 2007;BARFOD et al, 2011). Dentro desta família, o gênero Euterpe reúne 28 espécies (JARDIM, 2005), e destas, sete são distribuídas na América do Sul e Central, das quais seis são encontradas no Brasil: E. edulis, E. caatinga, E. oleracea, E. longebracteata, E. precatoria e E. espiritosantensis (PINATUD et al, 2008).…”
Section: Introductionunclassified